(untitled) (Journal of Mechanical Engineering, 2018)
Composite specimens are prepared by impregnating human hair in polyester resin. Randomly oriented chopped Human hair with varied weight ratios and Fiber lengths are used for the present experimental study. The composites are compression moulded using hand layup technique. An attempt is made to find out the influence of fiber weight ratio and length on the Tensile strength and tensile modulus. Optimum Fiber weight ratio and Fiber length are identified for maximizing the tensile strength and tensile modulus of the Human hair polyester composites. Experiments are carried out as per the standards and results are discussed. Further, Tensile stress and Tensile Modulus of the composite at optimum fiber length are estimated using different theoretical models and are compared with the experimental results.